PELANGGARAN PRINSIP KERJA SAMA DAN PEMATUHAN PRINSIP KESANTUNAN DALAM PEMBELAJARAN BAHASA INDONESIA DI SMK PELAYARAN âAKPELNIâ SEMARANG - Fajrin, Rafika; Andayani, Andayani; Rohmadi, Muhammad (Jurnal S2 Pendidikan Bahasa Indonesia, 2016)
This study aimed to describe the type of speech acts used in Indonesian language learning; violation of cooperation principleÂ in Indonesian language learning; and Compliance politeness principle in Indonesian language learning at SMK Pelayaran